إدارة الأزمات على المستوى المحلي بالجزائر -أزمة فيروس كورونا )كوفيد 19( نموذجا- - عدوم حميدة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف الدراسة إلى تقييم موضوع إدارة الأزمات على المستوى المحلي في الجزائر، وذلك بتحليل جملة من القوانين فيما يخص الجماعات المحلية (قانون 2011- المتعلق بالبلدية، وقانون 2012-07 المتعلق بالولاية)، وعليه تم اختيار أزمة كورونا – كوفيد 19 – كمثال لدراسة إدارة الأزمات على المستوى المحلي في الجزائر، وتقييمها ومعرفة مدى نجاحها محليا انطلاقا من المراسيم والقوانين التي أصدرتها الحكومة الجزائرية بخصوص إدارة هذه الأزمة الصحية. وعليه تقدم الدراسة بعض الاقتراحات العلمية لتقويم عمل الجماعات المحلية في الجزائر بأساليب علمية، تمكنها من مواجهة مختلف الأزمات التي ستعترضها مستقبلا. This study aims to assess the crisis management subject on the local level in Algeria, and that by analyzing a set of laws in relation to local groups (law 2010-10 related to municipal) and (law 2012-07 related to the state). And upon so, the covid-19 crisis has been chosen as an example to conduct a study on the crisis management on the local level, and assessing it to arrive at the length of its success locally, starting from the laws that has been issued by the Algerian government concerning this crisis. This study presents some suggestions to improve the work of the local groups in scientific manners to enable them to withstand the various crises in the future.